KOMBINASI KULIT BUAH JERUK PURUT DAN SELEDRI PADA PEMBUATAN TEH HERBAL - Jumardi Jumardi; Faizah Hamzah; Dewi Fortuna Ayu (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was to obtain a best combination of herbal tea from the skin of kaffir lime and celery to produce a good quality of herbal tea which preferred by the panelists. This research used a Completely Randomized Design with five treatments and three replications. The treatments used were combination of kaffir lime skin and celery 3:1, 2:1, 1:1, 1:2, and 1:3 in making herbal tea. Data were statistically analyzed with analysis of variance and Duncan’s New Multiple Range Test at 5% level. The results showed that kaffir lime skin and celery significantly effected water content, ash content, IC50, descriptive and hedonic tests on sensory assessment. Treatment chosen from the results was the treatment of kaffir lime skin and celery 1:3. This treatment had water content 7.56%, ash content 4.18%, and IC50 138.55 µg/mL. The results of the treatment chosen on descriptive test of tea were kaffir lime skin and celery flavour, rather brown colour, and rather astringent taste. The result of hedonic test showed that flavour and colour of tea were little bit preferred by panelists, taste was preferred, and assessment overall was little bit preferred by panelists. Keywords : kaffir lime skin, celery, antioxidants.